Diamond powder particles and preparation method thereof
By the use of the cymbal method on the surface of diamond powder particles to decompose the film covering method to form iron and nickel-carbon mutual diffusion layers and metal layers, the problem of poor combination of diamond powder particles and metal matrix Its adhesion and service life.
Patent Information
- Application Number
- CN202310036376.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-01-09
AI Technical Summary
In application, diamond powder particles have problems caused by poor bonding with matrix metals, easy oxidation, graphitization, and shedding caused by interface stress, which affects their use effect in the fields of friction, electronic packaging, aerospace, etc.
The pyramid method is used to decompose the film covering method, and the surface of the diamond powder particles forms a metal-carbon mutual diffusion layer and metal layer composed of iron and nickel, which improves its adhesion and wetability with the metal matrix.
It significantly improves the adhesion of diamond powder particles and metal substrates, prevent oxidation and graphization, enhance the interface binding force, and extend the service life of diamond-metal composite materials and devices.
Smart Images

Figure CN116117137B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface protection and modification of diamond powder particles, and in particular to diamond powder particles and a preparation method thereof. Background Art
[0002] Diamond crystals are composed of carbon atoms that are covalently bonded to each other. Each carbon atom is connected to four carbon atoms in the surrounding space in the crystal structure in the form of saturated covalent bonds, forming a regular tetrahedral structure. This structural feature makes diamond not only the hardest material in nature, but also has excellent thermal conductivity (2200W·m -1 ·K -1 ), low thermal expansion coefficient (0.86×10 -6 / ℃) and low density (3.52g·cm -3 ), is used in many important industrial fields, such as fine grinding, electronic packaging, various drill bits, wire drawing dies, and is also used as a component of many precision instruments.
[0003] In practical applications, diamond generally exists in the form of fine powder or granules. Due to the high interfacial energy between diamond and most metals, ceramics and other materials, they cannot effectively wet each other when forming a composite material, and the interface bonding is very poor. In the application field of friction, problems such as easy detachment from the base metal under the action of grinding force and rapid loss of diamond composite workpieces have occurred. In the application field of electronic packaging, there is a high interfacial thermal resistance at the interface between diamond and base metals such as copper and aluminum, which seriously affects the effective heat dissipation and service life of components in electronic packaging materials. At the same time, the thermal expansion coefficient of diamond is much lower than that of metal, which makes it easy to generate interfacial stress during the application process and causes bulging and shedding of the metal coating, which cannot meet the use requirements of fields such as aerospace with temperature cycle requirements.
[0004] In addition, the above-mentioned diamond tools and devices are mostly produced by powder metallurgy, and the sintering temperature is relatively high. When diamond is heated to about 700°C in air, it begins to lose weight due to oxidation, and its compressive strength decreases. At 1000°C, diamond begins to partially graphitize, which greatly reduces the use effect of diamond tools and devices. Therefore, how to improve the bonding and oxidation resistance of diamond to the matrix metal, and prevent diamond from falling off during use and oxidation and graphitization at high temperatures are problems that need to be solved in the use of diamond tools.
[0005] At present, the metal layer is generally formed on the surface in advance to improve the adhesion between diamond and base metal, prevent the diamond from falling off early, and better play the excellent performance of diamond. At the same time, the surface metallization method can also prevent the diamond from being oxidized, graphitized and corroded by chemical reactions. Coating a uniform metal layer with adjustable thickness and high bonding strength on the surface of diamond is an important basis for making full use of the excellent performance of diamond.
[0006] However, the affinity between pure metals and diamond is generally either too poor or too strong. Some highly thermally conductive metals such as silver, copper, and aluminum have poor interfacial wetting and poor interfacial bonding with diamond, resulting in composite materials with lower thermal conductivity, higher thermal expansion coefficient, and lower mechanical properties; while some other metals such as transition metals such as W, Cr, Ti, and Mo have strong reactivity with diamond (also known as strong carbide-forming elements). In recent years, around strong carbide-forming elements, some researchers have proposed using magnetron sputtering + vacuum heat treatment, sol-gel method + hydrogen reduction heat treatment method to coat a carbide layer including W, Cr, Ti, Mo, Zr and other elements on the surface of diamond, further improving the wettability between diamond and the metal matrix, thereby improving the thermal conductivity of the composite material (Zhang Di, Yuan Mengying, Tan Zhanqiu, et al. Research Progress on Thermal Conductivity Modification and Nano-Sized Interface of Diamond / Copper Composites [J]. Acta Metallurgica Sinica, 2018, 54(11): 1586-1596). They believe that the performance of metal carbides is not only between metals and diamonds, but can also improve the wettability of both. Moreover, carbides also have a protective effect, isolating direct contact with oxygen and preventing diamond from being oxidized at high temperatures. However, the interface bonding is too strong, which also makes the interface structure difficult to control and cracks easy to initiate, which in turn leads to shortcomings such as easy peeling of the coating layer under external force. At the same time, the carbide layer generated at the interface at high temperature is too thick, which increases the interface thermal resistance and reduces the thermal conductivity of the composite material. Moreover, metals such as W, Cr, and Ti are not stable enough at high temperatures and are easily dissolved into the metal matrix during the preparation of composite materials. The composite materials finally obtained often have loose interface bonding and interface debonding.
[0007] At present, the methods for metal-coated diamond powder particles can be selected from sol-gel method, diffusion method, impregnation-precipitation method, chemical plating, electroplating, physical vapor deposition method, chemical vapor deposition method and mechanical coating, etc. Although the sol-gel method can be evenly dispersed (such as invention patent 201410840747.8, process for coating composite film on diamond surface, discloses a process for coating composite film on diamond surface using sol-gel method), but the coating layer has the problem of incomplete coating, and the process is relatively cumbersome; the diffusion method has the problem of uneven coating (such as invention patent 201710024448.0, method for preparing diamond material coated on molybdenum carbide surface, provides a method for preparing diamond material coated on molybdenum carbide surface); impregnation and precipitation methods can generally only obtain powder with low content; both physical and chemical vapor deposition methods have high requirements for equipment; and the ball mill mechanical coating method is simple, but it is difficult to form coated powder. Chemical plating and electroplating are the more commonly used methods. The invention patent with patent number 201710176265.0 discloses a method of coating a nickel-phosphorus alloy protective coating on the surface of diamond by chemical plating. Patent CN102732764A discloses a method of copper plating on the surface of diamond powder particles by chemical plating process. The relevant patents further effectively combine chemical plating and microwave heating (such as the invention patent with application number 201810827267.6, a diamond surface metallization method with high bonding strength, and the invention patent with application number 201810826428.X, a method for preparing a diamond surface coated with Ni-WP metallized coating): first, a uniform and dense metal coating is plated on the diamond surface by chemical plating, and then a layer of microwave absorbent is coated on the surface of the diamond, and then the absorbent can be quickly heated by microwave heating technology, thereby accurately transferring heat to the chemical plating layer and diamond powder particles, so that a pre-designed carbide layer is formed between the two. However, both chemical plating and electroplating require complex sensitization and activation of the substrate, which is costly, highly polluting to the environment, slow and time-consuming, and easy to introduce other impurity elements during the plating process. Developing simple, cheap and effective diamond surface plating technology is still the direction that current researchers are committed to.
[0008] Metallic iron and nickel have good affinity with many metals and non-metals and are widely used as main alloying elements. Plating iron or nickel on the surface of diamond can improve the metal matrix's holding power on diamond, improve interface bonding, and thus increase the service life of the material in application. Moreover, metallic nickel has high oxidation resistance and corrosion resistance. However, although traditional electroplating and chemical plating methods can prepare metallic nickel film layers on the surface of diamond, there are problems such as high impurities (low purity) and complicated processes.
[0009] The carbonyl method is a refining method that uses the principle of chemical migration reaction. It is currently mainly used to produce high-purity nickel, iron, etc. Under normal pressure and 40-200℃ (nickel is 40-100℃; iron is 150-200℃), carbon monoxide can react with active metal nickel and iron to produce a colorless liquid - carbonyl nickel and iron. When the liquid is heated to 150-300℃ (nickel is 42.5-300℃; iron is 103.6-300℃), it can be decomposed into metallic nickel or iron and carbon monoxide. The reaction is as follows:
[0010] Ni+4CO=Ni(CO) 4 (liquid);Ni(CO) 4 =Ni(solid)+4CO↑
[0011] Fe+5CO=Fe(CO) 5 (liquid); Fe(CO) 5 =Fe(solid)+5CO↑
[0012] The nickel / iron in the surface layer of the nickel / iron coated powder produced by this method has high purity, and compared with other methods for manufacturing similar products, its process route is advanced, and has the advantages of energy saving, material saving, high quality, high raw material utilization, strong process controllability, and is conducive to mass production. Moreover, the process route adopted by this method does not produce wastewater, waste residue and polluting gas, and has environmental protection characteristics. Summary of the invention
[0013] The present invention provides a diamond powder particle and a preparation method thereof, a diamond powder particle coated with a film decomposed by a carbonyl method. The coated diamond powder particles are used to prepare a metal matrix composite material, and the coating layer can significantly improve the adhesion of the diamond to the metal substrate, protect the diamond from harmful chemical reactions with the metal matrix during the sintering process, improve the wettability of the two, increase the holding force of the metal matrix on the diamond, and improve the service life of the diamond-metal matrix composite device.
[0014] The technical solution adopted by the present invention is:
[0015] A diamond powder particle consists of a diamond powder particle and a coating layer coated on the surface of the diamond powder particle. The coating layer is a metal-carbon interdiffusion layer and a metal layer from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0016] Furthermore, the metal in the metal layer is one or more of iron and nickel, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer or the nickel layer and diamond.
[0017] Furthermore, the coating layer on the surface of the diamond powder particles has a thickness of 100-1000 nm, wherein the metal-carbon interdiffusion layer preferably has a thickness of 20-100 nm, and the average particle size of the diamond powder particles is 2.0-100.0 μm.
[0018] Furthermore, the metal layer preferably includes an inner layer and an outer layer, which are a metal iron layer and a metal nickel layer respectively, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the first deposited iron layer and diamond.
[0019] The method for preparing diamond powder particles, which uses a carbonyl method to decompose thin film-coated diamond powder particles, specifically comprises the following steps:
[0020] Step 1, ultrasonically cleaning the diamond powder particles in potassium hydroxide, dilute hydrochloric acid and dilute nitric acid solutions in sequence, and ultrasonically cleaning them in deionized water for 3-5 times after each cleaning, and then entering the next solution for cleaning;
[0021] After being cleaned with a dilute nitric acid solution, the obtained diamond powder particles are sequentially ultrasonically cleaned with deionized water and ethanol, and then dried to obtain activated clean diamond powder particles;
[0022] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0023] S1. Continuously inject gas at 200-350°C into the coating furnace for 0.1-10h and maintain a constant temperature;
[0024] S2, continuously injecting the carbonyl metal gas into the coating furnace for 1 to 10 hours, the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0025] Step 3, adjusting the gas temperature to 600°C and continuously injecting it into the coating furnace for 0.5 to 50 hours; when the deposited carbonyl metal is iron, preferably lowering the gas temperature to 200-350°C, and then introducing carbonyl nickel metal gas and gas for 0.1-50 hours;
[0026] Step 4: Inject gas at 200-350°C into the coating furnace for 0.1-1h, then stop injecting gas, and then inject nitrogen at 20-30°C to replace and sterilize the residual carbonyl metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen. Take out the treated film-coated diamond powder particles.
[0027] Furthermore, in step 1,
[0028] The concentration of potassium hydroxide solution is 1.8-4.5 mol / L, and ultrasonic cleaning is performed for 0.5-1h;
[0029] The concentration of the dilute hydrochloric acid solution is 1.2-1.7 mol / L, and ultrasonic cleaning is performed for 0.5-1h;
[0030] The concentration of dilute nitric acid used was 1.2-1.7 mol / L, and ultrasonic cleaning was performed for 0.5-1h;
[0031] The duration of each deionized water ultrasonic cleaning and ethanol ultrasonic cleaning is 0.5-1h;
[0032] The processing frequency of the above ultrasonic cleaning is 70-90KHz.
[0033] Furthermore, in step 2, the amount of the carbonyl metal gas corresponding to the mass of the diamond powder particles to be processed is 0.5-50m3 / kg; the carbonyl metal gas and the gas flow rate are 500-5000 liters / hour.
[0034] Furthermore, the gas is carbon monoxide, or an inert gas, or a mixed gas of an inert gas and one of carbon monoxide, acetylene and methane.
[0035] Among them, acetylene can be used simultaneously with inert gas or carbon monoxide in equal proportions, and methane can also be used simultaneously with inert gas or carbon monoxide in equal proportions.
[0036] Furthermore, the carbonyl metal gas is carbonyl iron metal gas or carbonyl nickel metal gas, which is produced by injecting carbonyl metal liquid into an evaporator and heating it at 50-300° C. to gasify it into carbonyl metal gas.
[0037] After adopting the above scheme, the present invention has the following beneficial effects:
[0038] First, the method of the present invention uniformly deposits an iron and / or nickel film with a thickness of 100-1000nm on the surface of diamond powder particles with an average particle size of 2.0-100.0μm by decomposing carbonyl metals, and then forms a diffusion layer of a certain thickness between the diamond powder particles and the deposited iron / or nickel film through a period of thermal diffusion process, thereby solving the problems of affinity, wettability, insufficient holding force, easy oxidation and graphitization of diamond powder particles with the matrix metal when used to prepare metal-based composite materials. Moreover, the above-mentioned deficiencies and problems can be further improved by designing the structure of the nickel metal layer on the bottom iron.
[0039] Second, the iron and nickel obtained by the invention are of high purity, with good process controllability and repeatability, and can be mass-produced industrially. At the same time, the diffusion layer process is further obtained through subsequent heat treatment and is completed in the same device, without the need for special additional equipment, and has the advantages of simple operation and high efficiency. Moreover, the present invention does not produce wastewater, waste residue and polluting gas, and has environmental protection characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a schematic diagram of the structure of diamond powder particles coated by film decomposition using the carbonyl method of the present invention;
[0041] Figure 2 This is a schematic diagram of the structure of diamond powder particles coated by carbonyl film decomposition in Example 12 of the present invention;
[0042] Figure 3 The XRD characterization results of diamond powder particles coated with iron thin film by carbonyl method in Example 4 of the present invention;
[0043] Figure 4 The XRD characterization results of diamond powder particles coated with nickel thin film by carbonyl method in Example 7 of the present invention;
[0044] Figure 5 This is the XRD characterization result of diamond powder particles coated with iron-nickel film using the carbonyl method in Example 12 of the present invention.
[0045] Specific reference numerals:
[0046] 1. Diamond powder particles; 2. Metal-carbon interdiffusion layer; 3. Metal iron layer; 4. Metal nickel layer; 5. Metal layer. DETAILED DESCRIPTION
[0047] The present invention is further described below in conjunction with embodiments and drawings.
[0048] Example 1
[0049] like Figure 1 As shown, the diamond powder particle 1 is composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 5 from the inner layer to the outer layer, and the outer layer structure covers the inner layer, the coating layer thickness on the surface of the diamond powder particle 1 is 1000nm, the average particle size of the diamond powder particles is 100.0μm, and the thickness of the metal-carbon interdiffusion layer 2 is 100nm.
[0050] The metal in the metal layer may be one or more of iron and nickel, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer or the nickel layer and diamond.
[0051] Example 2
[0052] like Figure 1As shown, the diamond powder particle 1 is composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 5 from the inner layer to the outer layer, and the outer layer structure covers the inner layer, the coating layer thickness on the surface of the diamond powder particle 1 is 100nm, the average particle size of the diamond powder particles is 2.0μm, and the thickness of the metal-carbon interdiffusion layer 2 is 20nm.
[0053] The metal in the metal layer may be one or more of iron and nickel, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer or the nickel layer and diamond.
[0054] Example 3
[0055] like Figure 1 As shown, the diamond powder particle 1 is composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 5 from the inner layer to the outer layer, and the outer layer structure covers the inner layer, the coating layer thickness on the surface of the diamond powder particle 1 is 500nm, the average particle size of the diamond powder particles is 20μm, and the thickness of the metal-carbon interdiffusion layer 2 is 40nm.
[0056] The metal in the metal layer may be one or more of iron and nickel, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer or the nickel layer and diamond.
[0057] Example 4
[0058] like Figure 1 and Figure 3 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0059] The coating layer on the surface of the diamond powder particles 1 has a thickness of 100 nm, the average particle size of the diamond powder particles is 2.0 μm, and the thickness of the metal-carbon interdiffusion layer is 20 nm.
[0060] The metal layer is a metal iron layer, the thickness of the metal iron layer is 80nm, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer and diamond.
[0061] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0062] Step 1, the diamond powder particles are ultrasonically cleaned in a solution with a concentration of 1.8 mol / L potassium hydroxide for 0.5 h, in a solution with a concentration of 1.2 mol / L dilute hydrochloric acid for 0.5 h, and in a solution with a concentration of 1.2 mol / L dilute nitric acid for 0.5 h, and after each cleaning, they are ultrasonically cleaned with deionized water for 3 times, with a total time of 0.5 h, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are ultrasonically cleaned with deionized water for 0.5 h, ultrasonically cleaned with ethanol for 0.5 h, and then dried to obtain activated clean diamond powder particles.
[0063] The processing frequency of the ultrasonic cleaning in step 1 is 70KHz.
[0064] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0065] S1, continuously inject 200°C carbon monoxide gas into the coating furnace for 0.1h, and keep the temperature constant during the period;
[0066] S2, injecting carbonyl iron metal liquid into an evaporator, and heating and vaporizing it at 110° C. to form carbonyl iron metal gas, and continuously injecting the carbonyl iron metal gas into the coating furnace for 1 hour, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0067] The gas consumption of carbonyl iron metal gas corresponding to the mass of diamond powder particles processed is 0.5m 3 / kg; the flow rate of carbonyl iron metal gas and carbon monoxide gas is 500 liters / hour.
[0068] Step 3, adjust the gas temperature to 600°C and continue to inject into the coating furnace for 0.5h;
[0069] Step 4: Inject 200°C gas into the coating furnace for 0.1h, then stop injecting gas, and then inject 20°C nitrogen to replace and disinfect the residual carbonyl iron metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0070] The coated diamond powder particles are composed of two phases, diamond and iron, using an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd., Japan. Although iron is coated on the outer surface of diamond, due to its small thickness, the diffraction peak of diamond in the XRD result is still the strongest.
[0071] Example 5
[0072] like Figure 1 and Figure 3As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0073] The coating layer on the surface of the diamond powder particles 1 has a thickness of 1000 nm, the average particle size of the diamond powder particles is 100.0 μm, and the thickness of the metal-carbon interdiffusion layer is 100 nm.
[0074] The metal layer is a metal iron layer, the thickness of the metal iron layer is 900nm, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer and diamond.
[0075] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0076] Step 1, the diamond powder particles are sequentially subjected to ultrasonic cleaning in a solution with a concentration of 4.5 mol / L potassium hydroxide for 1 hour, ultrasonic cleaning in a solution with a concentration of 1.7 mol / L dilute hydrochloric acid for 1 hour, and ultrasonic cleaning in a solution with a concentration of 1.7 mol / L dilute nitric acid for 1 hour, and after each cleaning, they are subjected to ultrasonic cleaning in deionized water for 5 times, with a total time of 1 hour, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are sequentially subjected to ultrasonic cleaning in deionized water for 1 hour, ultrasonic cleaning in ethanol for 1 hour, and then dried to obtain activated clean diamond powder particles.
[0077] The processing frequency of the ultrasonic cleaning in step 1 is 90KHz.
[0078] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0079] S1, continuously inject 350°C carbon monoxide gas into the coating furnace for 10 hours, during which the temperature is kept constant;
[0080] S2, injecting carbonyl iron metal liquid into an evaporator, and heating and vaporizing it at 150° C. to form carbonyl iron metal gas, and continuously injecting the carbonyl iron metal gas into the coating furnace for 10 hours, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0081] The gas consumption of carbonyl iron metal gas corresponding to the mass of diamond powder particles processed is 50m 3 / kg; the flow rate of carbonyl iron metal gas and carbon monoxide gas is 5000 liters / hour.
[0082] Step 3, adjust the gas temperature to 600°C and continue injecting into the coating furnace for 50 hours;
[0083] Step 4: Inject 350°C gas into the coating furnace for 1 hour, then stop injecting gas, and then inject 30°C nitrogen to replace and disinfect the residual carbonyl iron metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0084] The coated diamond powder particles are composed of two phases, diamond and iron, using an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd., Japan. Although iron is coated on the outer surface of diamond, due to its small thickness, the diffraction peak of diamond in the XRD result is still the strongest.
[0085] Example 6
[0086] like Figure 1 and Figure 3 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0087] The coating layer on the surface of the diamond powder particles 1 has a thickness of 500 nm, the average particle size of the diamond powder particles is 50 μm, and the thickness of the metal-carbon interdiffusion layer is 50 nm.
[0088] The metal layer is a metal iron layer, the thickness of the metal iron layer is 450nm, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the iron layer and diamond.
[0089] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0090] Step 1, the diamond powder particles are sequentially subjected to ultrasonic cleaning in a solution with a concentration of 3.2 mol / L potassium hydroxide for 0.7 h, a solution with a concentration of 1.5 mol / L dilute hydrochloric acid for 0.7 h, and a solution with a concentration of 1.4 mol / L dilute nitric acid for 0.7 h, and after each cleaning, they are subjected to ultrasonic cleaning in deionized water for 4 times, with a total time of 0.7 h, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are sequentially subjected to ultrasonic cleaning in deionized water for 0.7 h, ultrasonic cleaning in ethanol for 0.7 h, and then dried to obtain activated clean diamond powder particles.
[0091] The processing frequency of the ultrasonic cleaning in step 1 is 80KHz.
[0092] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0093] S1, continuously inject 300°C carbon monoxide gas into the coating furnace for 8 hours, and keep the temperature constant during the period;
[0094] S2, injecting carbonyl iron metal liquid into an evaporator, and heating and vaporizing it at 250° C. to form carbonyl iron metal gas, and continuously injecting the carbonyl iron metal gas into the coating furnace for 7 hours, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0095] The gas consumption of carbonyl iron metal gas corresponding to the mass of diamond powder particles processed is 30m 3 / kg; the flow rate of carbonyl iron metal gas and carbon monoxide gas is 3500 liters / hour.
[0096] Step 3, adjust the gas temperature to 600°C and continue injecting into the coating furnace for 40 hours;
[0097] Step 4: Inject 300°C gas into the coating furnace for 0.7h, then stop injecting gas, and then inject 25°C nitrogen to replace and disinfect the residual carbonyl iron metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0098] The coated diamond powder particles are composed of two phases, diamond and iron, using an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd., Japan. Although iron is coated on the outer surface of diamond, due to its small thickness, the diffraction peak of diamond in the XRD result is still the strongest.
[0099] Example 7
[0100] like Figure 1 and Figure 4 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0101] The coating layer on the surface of the diamond powder particles 1 has a thickness of 100 nm, the average particle size of the diamond powder particles is 2.0 μm, and the preferred thickness of the metal-carbon interdiffusion layer is 20 nm.
[0102] The metal layer is a metal nickel layer, and the corresponding thickness of the metal nickel layer is 80 nm. The metal-carbon interdiffusion layer is formed by the interdiffusion of the nickel layer and diamond.
[0103] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0104] Step 1, the diamond powder particles are ultrasonically cleaned in a solution with a concentration of 1.8 mol / L potassium hydroxide for 0.5 h, in a solution with a concentration of 1.2 mol / L dilute hydrochloric acid for 0.5 h, and in a solution with a concentration of 1.2 mol / L dilute nitric acid for 0.5 h, and after each cleaning, they are ultrasonically cleaned with deionized water for 3 times, with a total time of 0.5 h, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are ultrasonically cleaned with deionized water for 0.5 h, ultrasonically cleaned with ethanol for 0.5 h, and then dried to obtain activated clean diamond powder particles.
[0105] The processing frequency of the ultrasonic cleaning in step 1 is 70KHz.
[0106] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0107] S1, continuously inject argon gas at 200°C into the coating furnace for 0.1h, and keep the temperature constant during this period;
[0108] S2, injecting carbonyl nickel metal liquid into an evaporator, and heating and vaporizing it at 50° C. to form carbonyl nickel metal gas, and continuously injecting the carbonyl nickel metal gas into the coating furnace for 1 hour, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0109] The gas consumption of carbonyl nickel metal gas corresponding to the mass of diamond powder particles processed is 0.5m 3 / kg; the flow rate of carbonyl nickel metal gas and argon gas is 500 liters / hour.
[0110] Step 3, adjust the gas temperature to 600°C and continue to inject into the coating furnace for 0.5h;
[0111] Step 4: Inject 200°C gas into the coating furnace for 0.1h, then stop injecting gas, and then inject 20°C nitrogen to replace and disinfect the residual carbonyl nickel metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0112] The coated diamond is composed of two phases, diamond and nickel, using an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd. Although nickel is coated on the outer surface of diamond, due to its small thickness, the diffraction peak of diamond in the XRD result is still the strongest.
[0113] Example 8
[0114] like Figure 1 and Figure 4As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0115] The coating layer on the surface of the diamond powder particles 1 has a thickness of 1000 nm, the average particle size of the diamond powder particles is 100.0 μm, and the metal-carbon interdiffusion layer preferably has a thickness of 100 nm.
[0116] The metal layer is a metal nickel layer, the corresponding thickness of the metal nickel layer is 900nm, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the nickel layer and diamond.
[0117] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0118] Step 1, the diamond powder particles are sequentially subjected to ultrasonic cleaning in a solution with a concentration of 4.5 mol / L potassium hydroxide for 1 hour, ultrasonic cleaning in a solution with a concentration of 1.7 mol / L dilute hydrochloric acid for 1 hour, and ultrasonic cleaning in a solution with a concentration of 1.7 mol / L dilute nitric acid for 1 hour, and after each cleaning, they are subjected to ultrasonic cleaning in deionized water for 5 times, with a total time of 1 hour, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are sequentially subjected to ultrasonic cleaning in deionized water for 1 hour, ultrasonic cleaning in ethanol for 1 hour, and then dried to obtain activated clean diamond powder particles.
[0119] The processing frequency of the ultrasonic cleaning in step 1 is 90KHz.
[0120] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0121] S1. Continuously inject argon gas at 350°C into the coating furnace for 0.10 hours, and keep the temperature constant during the period;
[0122] S2, injecting carbonyl nickel metal liquid into an evaporator, and heating and vaporizing it at 300° C. to form carbonyl nickel metal gas, and continuously injecting the carbonyl nickel metal gas into the coating furnace for 10 hours, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0123] The gas consumption of carbonyl nickel metal gas corresponding to the mass of diamond powder particles processed is 50m 3 / kg; the flow rate of carbonyl nickel metal gas and argon gas is 5000 liters / hour.
[0124] Step 3, adjust the gas temperature to 600°C and continue injecting into the coating furnace for 50 hours;
[0125] Step 4: Inject 350°C gas into the coating furnace for 1 hour, then stop injecting gas, and then inject 30°C nitrogen to replace and disinfect the residual carbonyl nickel metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0126] The coated diamond is composed of two phases, diamond and nickel, using an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd. Although nickel is coated on the outer surface of diamond, due to its small thickness, the diffraction peak of diamond in the XRD result is still the strongest.
[0127] Example 9
[0128] like Figure 1 and Figure 4 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0129] The coating layer on the surface of the diamond powder particles 1 has a thickness of 700 nm, the average particle size of the diamond powder particles is 65 μm, and the preferred thickness of the metal-carbon interdiffusion layer is 50 nm.
[0130] The metal layer is a metal nickel layer, the corresponding thickness of the metal nickel layer is 750nm, and the metal-carbon interdiffusion layer is formed by the interdiffusion of the nickel layer and diamond.
[0131] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0132] Step 1, the diamond powder particles are ultrasonically cleaned in a solution with a concentration of 3.4 mol / L potassium hydroxide for 0.8 h, in a solution with a concentration of 1.6 mol / L dilute hydrochloric acid for 0.8 h, and in a solution with a concentration of 1.4 mol / L dilute nitric acid for 0.8 h, and after each cleaning, they are ultrasonically cleaned with deionized water for 4 times, with a total time of 0.8 h, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are ultrasonically cleaned with deionized water for 0.8 h, ultrasonically cleaned with ethanol for 0.8 h, and then dried to obtain activated clean diamond powder particles.
[0133] The processing frequency of the ultrasonic cleaning in step 1 is 80KHz.
[0134] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0135] S1, continuously inject argon gas at 300°C into the coating furnace for 5 hours, and keep the temperature constant during this period;
[0136] S2, injecting carbonyl nickel metal liquid into an evaporator, and heating and vaporizing it at 80° C. to form carbonyl nickel metal gas, and continuously injecting the carbonyl nickel metal gas into the coating furnace for 7 hours, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0137] Among them, the gas consumption of carbonyl nickel metal gas corresponding to the unit mass of diamond powder particles processed is 40m 3 / kg; the flow rate of carbonyl nickel metal gas and argon gas is 2500 liters / hour.
[0138] Step 3, adjust the gas temperature to 600°C and continue injecting into the coating furnace for 30 hours;
[0139] Step 4: Inject 300°C gas into the coating furnace for 0.5h, then stop injecting gas, and then inject 25°C nitrogen to replace and disinfect the residual carbonyl nickel metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0140] The coated diamond is composed of two phases, diamond and nickel, using an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd. Although nickel is coated on the outer surface of diamond, due to its small thickness, the diffraction peak of diamond in the XRD result is still the strongest.
[0141] Example 10
[0142] like Figure 2 and Figure 5 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0143] The coating layer on the surface of the diamond powder particles 1 has a thickness of 100 nm, the average particle size of the diamond powder particles is 2.0 μm, and the thickness of the metal-carbon interdiffusion layer is 20 nm.
[0144] The metal layer includes an inner layer and an outer layer, which are a metal iron layer and a metal nickel layer respectively. The corresponding thicknesses of the metal iron layer and the metal iron layer and the metal nickel layer are 20nm and 60nm respectively.
[0145] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0146] Step 1, the diamond powder particles are ultrasonically cleaned in a solution with a concentration of 1.8 mol / L potassium hydroxide for 0.5 h, in a solution with a concentration of 1.2 mol / L dilute hydrochloric acid for 0.5 h, and in a solution with a concentration of 1.2 mol / L dilute nitric acid for 0.5 h, and after each cleaning, they are ultrasonically cleaned with deionized water for 3 times, with a total time of 0.5 h, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are ultrasonically cleaned with deionized water for 0.5 h, ultrasonically cleaned with ethanol for 0.5 h, and then dried to obtain activated clean diamond powder particles.
[0147] The processing frequency of the ultrasonic cleaning in step 1 is 70KHz.
[0148] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0149] S1, continuously inject a mixture of carbon monoxide and argon at 200°C (volume ratio of 2:1) into the coating furnace for 0.1h, and keep the temperature constant during this period;
[0150] S2, injecting carbonyl iron metal liquid into an evaporator, and heating and vaporizing it at 120° C. to form carbonyl iron metal gas, and continuously injecting the carbonyl iron metal gas into the coating furnace for 1 hour, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0151] The gas consumption of carbonyl iron metal gas corresponding to the mass of diamond powder particles processed is 0.5m 3 / kg; the flow rates of carbonyl iron metal gas, carbonyl nickel metal gas and carbon monoxide gas are 500 liters / hour.
[0152] Step 3, adjusting the gas temperature to 600°C, continuously injecting the gas into the coating furnace for 0.5h, then injecting the carbonyl nickel metal liquid into the evaporator, heating and gasifying it at 80°C to form carbonyl nickel metal gas, and then injecting it into the coating furnace, keeping the carbonyl nickel metal gas and the mixed gas flowing for 0.1h, and then stopping the introduction of the carbonyl nickel metal gas;
[0153] Step 4: Inject a mixed gas at 200°C into the coating furnace for 0.1h, then stop injecting the gas, and then inject nitrogen at 20°C to replace and disinfect the residual carbonyl iron metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0154] The coated diamond powder particles are analyzed by an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd. of Japan. The coated diamond powder particles are composed of three phases: diamond, iron and nickel. Since the penetration depth of X-rays exceeds ten microns (much greater than the nickel layer and iron layer coated on the surface of diamond), the diffraction peak of diamond is still the strongest in the XRD results, the diffraction peak of nickel is weaker, and the diffraction peak of iron is the weakest.
[0155] Embodiment 11
[0156] like Figure 2 and Figure 5 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0157] The coating layer on the surface of the diamond powder particles 1 has a thickness of 1000 nm, the average particle size of the diamond powder particles is 100.0 μm, and the thickness of the metal-carbon interdiffusion layer is 100 nm.
[0158] The metal layer comprises an inner layer and an outer layer, which are a metal iron layer and a metal nickel layer respectively. The corresponding thicknesses of the metal iron layer and the metal iron layer and the metal nickel layer are 150 nm and 750 nm respectively.
[0159] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0160] Step 1, the diamond powder particles are sequentially subjected to ultrasonic cleaning in a solution with a concentration of 4.5 mol / L potassium hydroxide for 1 hour, ultrasonic cleaning in a solution with a concentration of 1.7 mol / L dilute hydrochloric acid for 1 hour, and ultrasonic cleaning in a solution with a concentration of 1.7 mol / L dilute nitric acid for 1 hour, and after each cleaning, they are subjected to ultrasonic cleaning in deionized water for 5 times, with a total time of 1 hour, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are sequentially subjected to ultrasonic cleaning in deionized water for 1 hour, ultrasonic cleaning in ethanol for 1 hour, and then dried to obtain activated clean diamond powder particles.
[0161] The processing frequency of the ultrasonic cleaning in step 1 is 90KHz.
[0162] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0163] S1. Continuously inject a mixture of carbon monoxide and argon at 350°C (volume ratio of 2:1) into the coating furnace for 10 hours, during which the temperature is kept constant;
[0164] S2, injecting carbonyl iron metal liquid into an evaporator, and heating and vaporizing it at 110° C. to form carbonyl iron metal gas, and continuously injecting the carbonyl iron metal gas into the coating furnace for 10 hours, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0165] The gas consumption of carbonyl iron metal gas corresponding to the mass of diamond powder particles processed is 50m 3 / kg; the flow rates of carbonyl iron metal gas, carbonyl nickel metal gas and carbon monoxide gas are 5000 liters / hour.
[0166] Step 3, adjusting the gas temperature to 600°C and continuously injecting it into the coating furnace for 50 hours, then injecting the carbonyl nickel metal liquid into the evaporator, heating it at 80°C to gasify it into carbonyl nickel metal gas, and then injecting it into the coating furnace, keeping the carbonyl nickel metal gas and the mixed gas flowing for 50 hours, and then stopping the introduction of the carbonyl nickel metal gas;
[0167] Step 4: Inject the mixed gas at 350°C into the coating furnace for 1 hour, then stop injecting the gas, and then inject nitrogen at 30°C to replace and disinfect the residual carbonyl iron metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0168] The coated diamond powder particles are analyzed by an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd. of Japan. The coated diamond powder particles are composed of three phases: diamond, iron and nickel. Since the penetration depth of X-rays exceeds ten microns (much greater than the nickel layer and iron layer coated on the surface of diamond), the diffraction peak of diamond is still the strongest in the XRD results, the diffraction peak of nickel is weaker, and the diffraction peak of iron is the weakest.
[0169] Example 12
[0170] like Figure 2 and Figure 5 As shown, the diamond powder particles 1 are composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer 2 and a metal layer 3 from the inner layer to the outer layer, and the outer layer structure covers the inner layer.
[0171] The coating layer on the surface of the diamond powder particles 1 has a thickness of 850 nm, the average particle size of the diamond powder particles is 60 μm, and the thickness of the metal-carbon interdiffusion layer is 50 nm.
[0172] The metal layer includes an inner layer and an outer layer, which are a metal iron layer and a metal nickel layer respectively. The corresponding thicknesses of the metal iron layer and the metal iron layer and the metal nickel layer are 180 nm and 620 nm respectively.
[0173] The method for preparing diamond powder particles is to decompose the diamond powder particles coated with a film by a carbonyl method, and specifically comprises the following steps:
[0174] Step 1, the diamond powder particles are sequentially subjected to ultrasonic cleaning in a solution with a concentration of 2.9 mol / L potassium hydroxide for 0.8 h, ultrasonic cleaning in a solution with a concentration of 1.4 mol / L dilute hydrochloric acid for 0.8 h, and ultrasonic cleaning in a solution with a concentration of 1.4 mol / L dilute nitric acid for 0.81 h, and after each cleaning, they are subjected to ultrasonic cleaning in deionized water for 4 times, with a total time of 0.8 h, and then enter the next solution for cleaning; after cleaning with the dilute nitric acid solution, the obtained diamond powder particles are sequentially subjected to ultrasonic cleaning in deionized water for 0.8 h, ultrasonic cleaning in ethanol for 0.8 h, and then dried to obtain activated clean diamond powder particles.
[0175] The processing frequency of the ultrasonic cleaning in step 1 is 80KHz.
[0176] Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows:
[0177] S1, continuously inject a mixture of carbon monoxide and argon at 300°C (volume ratio of 2:1) into the coating furnace for 8 hours, during which the temperature is kept constant;
[0178] S2, injecting carbonyl iron metal liquid into an evaporator, and heating and vaporizing it at 160° C. to form carbonyl iron metal gas, and continuously injecting the carbonyl iron metal gas into the coating furnace for 7 hours, so that the surface of the diamond powder particles is rapidly decomposed and a uniform metal coating layer is formed;
[0179] Among them, the gas consumption of carbonyl iron metal gas corresponding to the mass of diamond powder particles processed is 35m 3 / kg; the flow rates of carbonyl iron metal gas, carbonyl nickel metal gas and carbon monoxide gas are 2800 liters / hour.
[0180] Step 3, adjusting the gas temperature to 600°C, continuously injecting the gas into the coating furnace for 40 hours, then injecting the carbonyl nickel metal liquid into the evaporator, heating and vaporizing it at 80°C to form carbonyl nickel metal gas, and then injecting it into the coating furnace, keeping the carbonyl nickel metal gas and the mixed gas flowing for 35 hours, and then stopping the introduction of the carbonyl nickel metal gas;
[0181] Step 4: Inject a mixed gas at 280°C into the coating furnace for 0.7h, then stop injecting the gas, and then inject nitrogen at 25°C to replace and disinfect the residual carbonyl iron metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles.
[0182] The coated diamond powder particles are analyzed by an X-ray diffractometer (XRD) of the model SmartLab of Rigaku Co., Ltd. of Japan. The coated diamond powder particles are composed of three phases: diamond, iron and nickel. Since the penetration depth of X-rays exceeds ten microns (much greater than the nickel layer and iron layer coated on the surface of diamond), the diffraction peak of diamond is still the strongest in the XRD results, the diffraction peak of nickel is weaker, and the diffraction peak of iron is the weakest.
[0183] The mixed gas in Examples 10 to 12 may also be a mixed gas of carbon monoxide and acetylene in a volume ratio of 1:1, or a mixed gas of carbon monoxide and methane in a volume ratio of 1:1, or a technician in this field may adjust the volume ratio according to actual conditions.
[0184] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A diamond powder particle, characterized in that: The invention is composed of diamond powder particles and a coating layer coated on the surface thereof, wherein the coating layer is a metal-carbon interdiffusion layer and a metal layer from the inner layer to the outer layer, and the outer layer structure covers the inner layer, the metal layer includes two layers of a metal iron layer and a metal nickel layer, and the metal-carbon interdiffusion layer is formed by interdiffusion of the first deposited iron layer and the diamond; The method for preparing diamond powder particles, which uses a carbonyl method to decompose thin film-coated diamond powder particles, specifically comprises the following steps: Step 1, ultrasonically cleaning the diamond powder particles in potassium hydroxide, dilute hydrochloric acid and dilute nitric acid solutions in sequence, and ultrasonically cleaning them in deionized water for 3-5 times after each cleaning, and then entering the next solution for cleaning; After being cleaned with a dilute nitric acid solution, the obtained diamond powder particles are sequentially ultrasonically cleaned with deionized water and ethanol, and then dried to obtain activated clean diamond powder particles; Step 2: Place the clean diamond powder particles obtained in step 1 into a coating furnace for treatment. The specific operation is as follows: S1. Continuously inject gas at 200-350°C into the coating furnace for 0.1-10h and maintain a constant temperature; S2, continuously injecting carbonyl metal iron gas into the coating furnace for 1 to 10 hours, the surface of the diamond powder particles is rapidly decomposed and a uniform metal iron coating layer is formed; Step 3, adjusting the gas temperature to 600°C and continuously injecting it into the coating furnace for 0.5 to 50 hours; then lowering the gas temperature to 200-350°C and then introducing carbonyl nickel metal gas for 0.1 to 50 hours; Step 4, injecting gas at 200-350°C into the coating furnace for 0.1-1h, then stopping the gas injection, and then injecting nitrogen at 20-30°C to replace and sterilize the residual carbonyl metal gas in the coating furnace. When the temperature of the diamond and the furnace drops below 30°C, stop introducing nitrogen and take out the treated film-coated diamond powder particles; Among them, the gas described in S1 in step 2, the gas described in step 3 and the gas described in step 4 are all carbon monoxide, or an inert gas, or a mixed gas of an inert gas and one of carbon monoxide, acetylene and methane.
2. The diamond powder particles according to claim 1, characterized in that: The coating layer on the surface of the diamond powder particles has a thickness of 100-1000 nm, the average particle size of the diamond powder particles is 2.0-100.0 μm, and the thickness of the metal-carbon interdiffusion layer is 20-100 nm.
3. The method for preparing diamond powder particles according to claim 1, characterized in that: In step 1, The potassium hydroxide solution has a concentration of 1.8-4.5 mol / L and is ultrasonically cleaned for 0.5-1 h; The concentration of the dilute hydrochloric acid solution is 1.2-1.7 mol / L, and ultrasonic cleaning is performed for 0.5-1h; The concentration of the dilute nitric acid solution is 1.2-1.7 mol / L, and ultrasonic cleaning is performed for 0.5-1h; The duration of each deionized water ultrasonic cleaning and ethanol ultrasonic cleaning is 0.5-1h; The processing frequency of the above ultrasonic cleaning is 70-90KHz.
4. The method for preparing diamond powder particles according to claim 1, characterized in that: In steps 2 and 3, the amount of carbonyl metal iron or nickel gas corresponding to the mass of diamond powder particles to be processed is 0.5-50m 3 / kg, gas flow rate is 500-5000 liters / hour.
5. The method for preparing diamond powder particles according to claim 1, characterized in that: The carbonyl metal iron or nickel gas is produced by injecting carbonyl metal iron or nickel liquid into an evaporator and heating it at 50-300° C. to vaporize it into carbonyl metal iron or nickel gas.
Citation Information
Patent Citations
Preparation method for diamond / copper composite material with high heat conductivity and low thermal expansion coefficient
CN102732764A
Technology of Coating Composite Thin Film on Diamond Surface
CN104479423B
Preparation method for diamond material coated with molybdenum carbide on surface
CN106676309A
Diamond surface magnetic plating and plating method thereof
CN106894075A
Preparation method of diamond surface coated Ni-W-P metal plating layer
CN108914096A